Spinal-cord compression in myeloma. Issue 6177 (9th June 1979) - Benson, W J; Scarffe, J H; Todd, I D; Palmer, M; Crowther, D
Abstract : Clinical records of 47 patients in whom spinal-cord compression was the presenting feature of plasma-cell myeloma were analysed retrospectively. Patients were referred during 1954-78. Median survival was 30 months and prognosis was best for those in whom the site of cord compression was the thoracic region. Early laminectomy and decompression followed by adequate radiotherapy resulted in complete or good partial response in over a third of patients who presented with complete paraplegia. Improvements in supportive care and more effective chemotherapy allow spinal-cord compression in myeloma to be treated promptly and vigorously, thus improving duration and quality of survival in a substantial proportion of patients.